Pandemic Procedures: Adapting Problem-Solving Court (PSC) Operations and Treatment Protocols During COVID-19 - Smith, Lindsay R. (Journal of drug issues, 2023)
With an ongoing pandemic claiming hundreds of lives a day, it is unclear how COVID-19 has affected court operations, particularly problem-solving courts (PSCs) which have goals rooted in rehabilitation for participants in their programs. Even with practical recommendations from national organizations directing courts on how to manage COVID-19, whether and how PSCs met the needs of PSC participants during this time is underexplored. This study, drawn from a larger national study using a survey of PSC coordinators, examines the COVID-19 responses of PSCs to remain safely operational for participants. A sub-sample of survey respondents (n = 82 PSC coordinators) detailed how the COVID-19 pandemic led to changes to their court and treatment operations amidst the constraints of the pandemic. The courts’ shifts in policy and practice have important impacts for court participants’ treatment retention and success in the PSC program, and these shifts need more in-depth research in the future.